379 Communicating a Traumatic Brain Injury Patient's Potential Need for Operative Intervention: The Surgical Intervention for Traumatic Injury Scale. (1st August 2016) - Sribnick, Eric Anthony; Shi, Junxin; Lunney, Michael P.; Dhall, Sanjay S.; Allen, Jason W.; Wright, David W.; Wheeler, Krista; Xiang, Huiyun
Abstract: INTRODUCTION: Severity scoring systems facilitate communication in many areas of medicine (eg, Glasgow Coma Scale [GCS] in neurological injury). However, there is no widely used scale to provide a tool for communicating the urgency of possible surgical intervention in patients with traumatic brain injury (TBI). This study builds on prior research to develop a scoring system for nonsurgical clinicians to communicate the potential need for surgical decompression in TBI patients. This scoring system, named the Surgical Intervention for Traumatic Injury (SITI), was designed to be comprehensive and easy to use. METHODS: The SITI scale ranks specific radiographic and clinical findings to assess the possible need for urgent surgical intervention. The scale includes: GCS (GCS >12 = 0 points, GCS 9-12 = 1 point, and GCS <9 = 2 points), pupil examination (unilateral enlarged pupil = 2 points), computed tomography findings (midline shift <5 mm = 0 points, 5-10 mm = 2 points, and >10 mm = 4 points), the presence of temporal pathology (1 point), and epidural hematoma (hematoma = 10 mm = 2 points). To validate the scale, the patient database for the Progesterone for the Treatment of Traumatic Brain Injury III Trial (PROTECT III) was used, and 871 patients were included in the analysis. We used the area under the receiver operating characteristic curve (ie area under the curve analysis) to further validate the SITI scale. RESULTS: Of the 871 patients reviewed, 159 underwent craniotomy, and 712 were treated nonoperatively. The mean SITI score was 5.3 for operative patients and 2.4 for nonoperative patients ( P < .001). We found that, applying a cutoff at a SITI score of 3 or greater, resulted in an area under the curve of 0.887. CONCLUSION: The SITI scale was designed to be a simple, objective system for communication between clinical services regarding the potential need for surgical decompression for TBI. Application of the SITI scale to the PROTECT III database demonstrates that a SITI score of 3 or more correlated well with the patient receiving a craniotomy. These results further demonstrate the potential utility of the SITI scale in clinical practice.